2010
DOI: 10.2174/092986710792231950
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Natural and Synthetic Antioxidants Important for Health and Longevity

Abstract: Reactive oxygen species (ROS) generated in the presence of O(2) by mitochondria, phagocytic cells, peroxisomes, and cytochrome P450 enzymes under physiological conditions, may play a dual function in the human organism. On the one hand, they participate in cell signal transduction cascades, leading to the activation of some transcription factors responsible for regulating of the expression of genes relevant for cell growth and differentiation. On the other hand, they cause oxidative damage of cellular DNA, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(106 citation statements)
references
References 246 publications
0
96
0
10
Order By: Relevance
“…Previous work has demonstrated that a high dose of Resveratrol is able to induce apoptosis and cell cycle arrest of human T24 bladder [9]. However, there are a lot of reports describing the dual effects of Resveratrol on cell viability on dose-dependent manner, including normal and cancer cells [3,10,19,20,22]. Thus, the aim of the present study was to evaluate the effects of Resveratrol, at low and high doses, on cell viability of bladder carcinoma cell line ECV304 during an oxidative stress condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated that a high dose of Resveratrol is able to induce apoptosis and cell cycle arrest of human T24 bladder [9]. However, there are a lot of reports describing the dual effects of Resveratrol on cell viability on dose-dependent manner, including normal and cancer cells [3,10,19,20,22]. Thus, the aim of the present study was to evaluate the effects of Resveratrol, at low and high doses, on cell viability of bladder carcinoma cell line ECV304 during an oxidative stress condition.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) have been regarded as toxic products of metabolism because of their damaging effects on structural and functional molecules that, eventually, result in apoptosis and uncontrolled proliferation [25]. Although, Resveratrol has induced secretion of ROS from ECV304, it protected them from exogenous oxidative stress such as other natural antioxidants from vegetable foods that can counteract the effects of ROS [22]. Our group has demonstrated previously that soy extracts are also apt to activate NO synthesis in ECV304 cells and to protect them against cell damage [26].…”
Section: Discussionmentioning
confidence: 99%
“…The application of enzyme antioxidants is limited because of the poor stability and ease of inactivation (Wojcik et al, 2010). However, when culturing mouse HSC in the presence of catalase, the number of short-term or long-term HSC with LSK immune markers was significantly increased and the stem cells begin to degenerate as the catalase is removed (Gupta et al, 2006).…”
Section: Oxygen Reactive Oxygen Species and Antioxidantsmentioning
confidence: 99%
“…산화적 스트레스가 병적 인 상태를 유발하게 되면, 체내 항산화 시스템은 산화적 스트 레스를 제거하여 항상성을 유지하게 한다. 인체내 superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT) 등을 포함하는 항산화 관련 해독 효소 및 Vitamin C, α-tocopherol 등을 포함하는 항산화 물질들이 존재한다 [4][5][6][7][8] . 이러한 항산화 효소 및 물질은 체내 대사과정에 서 발생되는 활성산소를 적극적으로 억제함으로써, 이를 손상 시키는 체외의 어떤 요인이 발생하지 않을 경우 산화-환원의 균형을 유지한다.…”
Section: 서 론 1)unclassified